Optimization of the Samapta Patrol Unit to Prevent the Crime of Theft by Weighting in the Jurisdiction of the Blitar Police - Habib, Fadhlan (Advances in Police Science Research Journal, 2024)
Abstract The high incidence of criminal acts of theft with weights in Blitar Regency has raised concerns for the local community. To prevent this, the National Police through the Blitar Police Samapta Patrol Unit carries out patrol activities. This research aims to identify how optimizing Samapta patrols can reduce the number of incidents of weighted theft in the Blitar Police jurisdiction. A qualitative approach and field research methods were used in this research, with data collection techniques through interviews, observation and document study. The data is then analyzed through data collection, data reduction, data presentation, and drawing conclusions. In this research, related conceptual literature was also used, such as the optimization concept, the concept of weighted theft, the crime prevention concept, the patrol concept, and POAC and 4M management theories. The results of the research show that the implementation of patrols by the Blitar Police Samapta Patrol Unit is still not optimal in preventing criminal acts of theft with weights due to internal and external factors that influence it. Improvements are needed to these factors so that patrol units can minimize incidents of cheating crimes in the Blitar Police jurisdiction more effectively.